COLOR HEALING: THE BALINESE MANDALA COLOR IN PAINTING PRACTICE - wayan Karja (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2021)
Abstract Color is very essential in life; it is hard to imagine this world without color or only black and white. All colors appear between black and white because they exist due to the effects of light and energy. This article focuses on how to use color as a medium of healing. The color of the Balinese mandala in form of the circle color wheel, each direction has its color, meaning, gods, place in the body, day, and number. The color is related to balance human emotion and healing psychology. Psychology is part of the field of science and applied science about human behavior, mental function, and mental processes. At first, color healing is only considered as a discourse in the development of visual art, but over time, gradually the understanding of using color healing began to develop. Painting becomes a pleasure that is very useful in developing and exploring various layers of life, both physically, mentally, emotionally, and spiritually. The main methods of using color as healing are play, flow, and freedom. There are several steps I used to practice using color healing; (1) study the psychological level of feelings of the participant; (2) classify the problem and search for the methods of expression; (3) interpretation and analysis of the artworks produced by participants; and (4) interpreting the colors and interviewing according to the participant's needs. In this case, the aspects of generating internal awareness and high sensitivity within the participant become the main focus. Keywords: painting, color, and healing.